2013
DOI: 10.1159/000358818
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Erythromycin and Rifampicin on Immunomodulatory Gene Expression and Cellular Function in Human Polymorphonuclear Leukocytes

Abstract: Background: We investigated the effects of two antibiotics, erythromycin and rifampicin, on the immunomodulatory gene expression and cellular function of human polymorphonuclear leukocytes (PMNs). Methods: We used real-time quantitative PCR to examine the expression of immunomodulatory genes. The production of reactive oxygen species (ROS) was determined by fluorescence-activated cell sorting. PMN chemotaxis was analyzed using a KK chemotaxis chamber. Results: Stimulation of PMNs with lipopolysaccharide (LPS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 58 publications
(28 reference statements)
1
12
0
2
Order By: Relevance
“…Although not a first line treatment for CD, rifampin is an effective second line treatment for CD [49]. In one study of 180 isolates of pathogenic CD from Canada and Italy, only 10% were resistant to rifampin [50]. The author has seen only 2 case of CD develop in over 800 patients treated with clindamycin and rifampin.…”
Section: Clostridium Difficile Colitismentioning
confidence: 99%
“…Although not a first line treatment for CD, rifampin is an effective second line treatment for CD [49]. In one study of 180 isolates of pathogenic CD from Canada and Italy, only 10% were resistant to rifampin [50]. The author has seen only 2 case of CD develop in over 800 patients treated with clindamycin and rifampin.…”
Section: Clostridium Difficile Colitismentioning
confidence: 99%
“…As an example, in vitro studies have shown that rifampicin results in less release of LTA and pro-inflammatory compounds from Streptococcus pneumoniae than the β-lactam antibiotics ceftriaxone or meropenem, despite similar bacterial killing effects 14 . Furthermore, rifampicin may reduce the inflammatory response by down-regulating the expression of pro-inflammatory pattern recognition receptors 15 . The killing of S. pneumoniae commences instantly after therapeutic drug concentrations are achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these antimicrobial properties, their therapeutic efficacies as anti-inflammatory agents have also been demonstrated in patients with chronic rhinosinusitis [3], diffuse panbronchiolitis [4], chronic obstructive pulmonary disease [5], and cystic fibrosis [6]. According to several in vitro studies, macrolide antibiotics, such as clarithromycin, azithromycin, and erythromycin, suppress the production of proinflammatory cytokines from leukocytes and thus exert immunomodulatory effects [7,8,9]. In previous in vivo studies in humans and experimental animal models, macrolide antibiotics have also been effective in the treatment of atopic dermatitis or bronchial asthma [10,11].…”
Section: Introductionmentioning
confidence: 99%